(untitled) (International Journal of Engineering Sciences & Management Research, 2017)
This paper find out the result of an experimental study performed to determine the performance of domestic refrigerator when a liquefied petroleum gas (LPG) which is locally available which comprises of 24.2% propane, 57.6% butane and 17.2% isobutene which is change from company to company is used as a Refrigerant. The LPG is cheaper and possesses an environmental friendly nature with zero Ozone Depletion Potential (ODP) and no Global Warming Potential (GDP). It is used in world for cooking activity. The refrigerator is designed to work on LPG. The performance parameters investigated is the refrigeration effect in specific time. The refrigerator worked efficiently when LPG was used as a refrigerant in the place of R134a. The evaporator temperature reached 4ᵒC with an ambient temperature of 36ᵒC. Also from the experiment which done in atmospheric condition, we can determine the optimum value of cooling effect with the suitable operating condition of regulating valve and capillary tube of the system.